Good governance for prison health in the 21st century. A policy brief on the organization of prison health (World Health Organization, 2013)
Against the background of concern about ministerial responsibility for the health of prisoners in Europe, the members of the WHO European Network on Prison and Health asked the WHO Regional Office for Europe to provide a document on the governance of prison health. A special Expert Group for the Stewardship of Prison Health and members of the WHO European Network on Prison and Health have contributed to this document. The Expert Group concluded, with regard to institutional arrangements for prison health, that: (i) managing and coordinating all relevant agencies and resources contributing to the health and well-being of prisoners is a whole-of-government responsibility, and (ii) health ministries should provide and be accountable for health care services in prisons and advocate healthy prison conditions. The Expert Group considers that such governance of prison health is in accordance with and supportive of the new European policy for health, Health 2020, and will lead to better health and well-being of prisoners as part of better public health.
Keywords: řízení zdravotnictví; Health Services Administration; Prisons; management, organizace a řízení zdravotnictví; věznice; Human Rights; zdravotní politika; Health Planning; vězni; lidská práva; Prisoners; Public Health; Health Policy; zdravotnické plánování; veřejné zdravotnictví